Important considerations in drug testing: Hydration state, sample volume, sample concentration and individual variation - Gill, N.; Weatherby, R.; Zhou, S.; Blazevich, A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
In modern day competition the use of performance enhancing drugs is a common occurrence in the optimization of athletic performance. To discourage drug use it is important to establish testing methods and programs that are effective and fair. Currently results of urine tests on athletes are based on concentration data, which may lead to incorrect conclusions for test results. The purpose of the present study was to investigate the excretion of a higher-than-therapeutic dose of Pseudeoephedrine (PSE) in urine and to monitor the excretion over 14 hours. Three subjects participated in two conditions: normal state (fluid intake of subject was similar to their normal regime) and hydrated state (500mL water every hour for 8 hours). Subjects provided samples at regular intervals over the 14-hour period. The urine samples were measured for volume, specific gravity (only two giving values not acceptable by "drug testers") and the concentration of PSE determined. Currently a concentration cut-off of 10 m g/mL is used for PSE.